The role of certain arthropods in the transmission of raillietina garrisoni. - Cruzada, Shirley F.
Experimental laboratory infections were carried out on laboratory-reared nymphs of Periplaneta australasiea (cockroach), adult Tribolium castaneum (flour beetles) and maggots of Musca domestica vicina (common housefly) to determine the role of these arthropods in the transmission of Raillietina garrisoni (common rat tapeworm). A total number of 250 per insect species were experimentally allowed to feed on ova teased from gravid segments of R. garrisoni dissected from the intestines of naturally-infected wild norway rat, Rattus norvegicus. The arthropods were colonized and maintained in the laboratory under room temperature. Dissections of the intestines of 1 set each of the 3 different insect species 1 hour after feeding revealed that R. garrisoni ova were ingested by Periplaneta australasiae and Tribolium castaneus but not by Musca domestica vicina. On the 10th day of dissection cysticercoid larvae of R. garrisoni were 1st observed from the homocoel of T. castaneum. Mature cysticercoid larvae were observed on the 15th day. Cysticercoid larvae were continually observed up to the 24th day after which most of the flour beetles died presumably due to the infection. Cysticercoid larvae were never observed in Periplaneta australasiea and Musca domestica vicina. Aside from infecting the 3 insect species, 2 groups of laboratory-bred white rats at 15 rats per group were also experimentally infected to follow the life cycle of R. garrisoni. 1 group white rats was infected with gravid segments of R. garrisoni (direct infected) obtained from dissections of naturally-infected wild norway rats. The other group of white rats was infected with mature cysticercoid larvae (indirect infection) dissected from laboratory-infected T. castaneum. The group of directly-infected white rats failed to support the developmental cycle of R. garrisoni under the conditions of the experiment. No developing forms of R. garrisoni were seen even after 2 months of infection. The group of indirectly-infected white rats ably supported the developmental cycle of R. garrisoni. 60 of the cysticercoid larvae given to the white rats by the stomach-tube method were able to survive and attach themselves in the small intestines and became adults in 2 months' time. Thus, the life cycle of R. garrisoni has been established for the 1st time.